Inorganic particle composite polymer film as well as preparation method and application thereof

Through the preparation method of inorganic particle composite polymer film, ultrasonic atomization assists in non-solvent-induced phase conversion, the problem of poor pore structure of the hydrogen-making membrane with alkaline electrolytic water is solved, and the electrolyte transmission performance and gas barrier performance are achieved, and the hydrogen production efficiency and safety are improved.

CN119800440APending Publication Date: 2025-04-11华能张掖能源有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411717643.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-11

Smart Images

  • Figure CN119800440A_ABST
    Figure CN119800440A_ABST
Patent Text Reader

Abstract

The invention provides an inorganic particle composite polymer film as well as a preparation method and application thereof. The preparation method of the inorganic particle composite polymer film comprises the following steps: S1, adding a film-forming polymer and inorganic particles into an organic solvent to form a film casting solution; s2, coating the surface of at least one side of the supporting layer with the membrane casting liquid to form a first membrane body carrying a wet membrane of the membrane casting liquid; s3, carrying out ultrasonic atomization treatment on the first membrane body, so that atomized water drops are in wet membrane contact with the membrane casting solution at the production speed of 0.5 L / h-20 L / h, and obtaining a second membrane body; and S4, carrying out water bath treatment on the second membrane body to obtain the inorganic particle composite polymer membrane. The invention provides a method for preparing an inorganic particle composite polymer membrane based on ultrasonic atomization assisted non-solvent induced phase inversion, and the pore structure of the obtained composite membrane has the characteristics of strong pore channel connectivity, small overall pore size and narrow pore size distribution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of hydrogen production by electrolysis of water, and in particular to an inorganic particle composite polymer membrane, a preparation method and application thereof. Background Art

[0002] As a highly potential energy carrier and raw material, hydrogen energy can be applied to energy, transportation, chemical industry, steel and other fields. Using renewable energy such as solar energy, wind energy, and hydropower to electrolyze water to produce hydrogen is an efficient hydrogen production strategy with zero carbon emissions. Compared with proton exchange membrane (PEM) water electrolysis, anion exchange membrane (AEM) water electrolysis and solid oxide water electrolysis (SOE), alkaline water electrolysis (AWE) has the advantages of low manufacturing cost, high technical reliability and good stability. It is considered to be the only technology solution that can achieve large-scale, low-cost renewable energy water electrolysis to produce hydrogen. As the core material of the alkaline electrolyzer, the diaphragm plays the role of transmitting electrolyte and blocking hydrogen and oxygen gases.

[0003] Therefore, for the alkaline water electrolysis process, the performance of the diaphragm in the electrolyzer has an important influence on the efficiency and safety of the electrolyzer. In the early days, the diaphragm used for hydrogen production by alkaline water electrolysis was mainly asbestos diaphragm, but asbestos is easy to swell in alkaline electrolyte, and asbestos is carcinogenic, so it has been gradually eliminated by the market. In recent years, industrial alkaline electrolyzers have begun to generally use woven polyphenylene sulfide diaphragms (i.e., PPS diaphragms), which have excellent heat resistance, high mechanical strength, and excellent electrical properties. However, in actual applications, it is found that the poor hydrophilicity of the PPS diaphragm will cause the internal resistance of the electrolyzer to be too large, the energy consumption of hydrogen production remains high, and the cost of hydrogen production is difficult to reduce; and the woven pore structure is difficult to effectively block the gas, resulting in low hydrogen purity and safety issues. In the case of large-scale application of alkaline water electrolysis hydrogen production, economy and safety are the most important considerations. Therefore, the industry urgently needs to develop new diaphragm materials with both low resistance and high gas barrier properties to support the upgrading of alkaline water electrolysis hydrogen production technology and equipment.

[0004] Based on this, how to design a preparation method for the diaphragm used for hydrogen production by water electrolysis, so as to optimize the pore structure of the resulting diaphragm and further improve its electrolyte transport performance and gas barrier performance, is one of the important technical problems that need to be solved in this field. Summary of the invention

[0005] The main purpose of the present invention is to provide an inorganic particle composite polymer membrane, a preparation method and application thereof, so as to solve the problems in the prior art that the diaphragm used for hydrogen production by electrolysis of water has poor pore structure, and the electrolyte transmission performance and gas barrier performance need to be improved.

[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing an inorganic particle composite polymer membrane, comprising: step S1, adding a film-forming polymer and inorganic particles into an organic solvent to form a casting liquid; step S2, coating the casting liquid on at least one side surface of a support layer to form a first membrane body carrying a wet film of the casting liquid; step S3, performing ultrasonic atomization treatment on the first membrane body so that the atomized water droplets contact the wet film of the casting liquid at a production rate of 0.5L / h to 20L / h to obtain a second membrane body; step S4, performing water bath treatment on the second membrane body to obtain an inorganic particle composite polymer membrane.

[0007] Furthermore, in step S3, the production rate of atomized water droplets is 5L / h to 15L / h; preferably, the ambient humidity of the ultrasonic atomization treatment is 30% to 98%, more preferably 50% to 90%.

[0008] Furthermore, the ultrasonic atomization treatment time is 0.1 min to 10 min, and the temperature is 25°C to 90°C, preferably 25°C to 35°C.

[0009] Furthermore, the temperature of the water bath treatment is 15°C to 60°C, preferably 20°C to 30°C.

[0010] Furthermore, the film-forming polymer is a polysulfone polymer, preferably one or more of polysulfone, polyethersulfone and polyphenylsulfone, and more preferably polysulfone; the organic solvent is a good solvent for polysulfone polymers, preferably one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and N,N-dimethylformamide.

[0011] Furthermore, the inorganic particles are selected from one or more of zirconium dioxide, cerium dioxide, titanium dioxide and barium sulfate, preferably zirconium dioxide; and / or the particle size of the inorganic particles is 20nm~200nm, preferably 50nm~100nm; and / or the weight ratio of the inorganic particles to the film-forming polymer is (5.0~6.0):1, and the weight ratio of the film-forming polymer to the organic solvent is 1:(5.5~6.0); the thickness of the support layer is 50μm~300μm, and the support layer is a wire mesh structure and / or a non-woven fabric structure, preferably a wire mesh structure; more preferably, the support layer material is selected from one or more of polyphenylene sulfide, polypropylene and polytetrafluoroethylene.

[0012] Furthermore, step S1 also includes: step S1-1, dissolving the film-forming polymer in an organic solvent to form a polymer solution; step S1-2, adding inorganic particles to the polymer solution, and obtaining a casting solution after mixing; preferably, the mixing is achieved by stirring and / or ball milling; preferably, the mixing is achieved by stirring, and the stirring rate is 100r / min to 1000r / min, and the time is 24h to 72h.

[0013] Furthermore, before coating, step S2 also includes degassing the casting solution; preferably, the degassing treatment is stirring degassing and / or vacuum degassing; more preferably, the degassing treatment is vacuum degassing, and the degassing time is 2h to 24h.

[0014] The second aspect of the present invention provides an inorganic particle composite polymer membrane, which is prepared by the above-mentioned method for preparing an inorganic particle composite polymer membrane. The inorganic particle composite polymer membrane has a porous structure with a pore size of 20nm to 500nm and a porosity of 60% to 90%.

[0015] The third aspect of the present invention provides an application of the above-mentioned inorganic particle composite polymer membrane as an alkaline electrolytic cell diaphragm material in the field of hydrogen production by water electrolysis.

[0016] The technical solution of the present invention provides a method for preparing an inorganic particle composite polymer membrane based on ultrasonic atomization-assisted non-solvent-induced phase transformation, which is simple to prepare and easy to scale up industrially. By introducing ultrasonic atomization treatment, the liquid membrane undergoes vapor-induced phase transformation, and a nanoscale three-dimensional interconnected sponge pore structure diaphragm is prepared without any additives, and the diaphragm surface is lace-like nanopores. The pore structure of the obtained composite membrane has the characteristics of strong pore connectivity, small overall pore size and narrow pore size distribution. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0018] Figure 1 The cross-sectional microscopic morphology of the inorganic particle composite polymer film prepared in Example 1, wherein 1a and 1b represent the morphology at different magnifications, respectively;

[0019] Figure 2 The surface microscopic morphology of the inorganic particle composite polymer film prepared in Example 1, wherein 2a and 2b respectively represent the morphology at different magnifications;

[0020] Figure 3 This is a cross-sectional microscopic morphology of the diaphragm obtained in Comparative Example 3;

[0021] Figure 4 This is the surface microscopic morphology of the diaphragm obtained in Comparative Example 3. DETAILED DESCRIPTION

[0022] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0023] As described in the background technology, the diaphragm used for hydrogen production by electrolysis of water in the prior art has the problems of poor pore structure, electrolyte transmission performance and gas barrier performance to be improved. In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing an inorganic particle composite polymer membrane, comprising: step S1, adding a film-forming polymer and inorganic particles to an organic solvent to form a casting liquid; step S2, coating the casting liquid on at least one side surface of the support layer to form a first membrane body carrying a wet film of the casting liquid; step S3, ultrasonically atomizing the first membrane body so that the atomized water droplets are in contact with the wet film of the casting liquid at a production rate of 0.5L / h to 20L / h to obtain a second membrane body; step S4, water bathing the second membrane body to obtain an inorganic particle composite polymer membrane.

[0024] The preparation method of the inorganic particle composite polymer membrane (hereinafter referred to as composite membrane) provided by the present invention is based on ultrasonic atomization-assisted non-solvent induced phase transformation. By introducing ultrasonic atomization treatment during the solidification process of the first membrane body, that is, the liquid membrane, the liquid membrane undergoes vapor-induced phase transformation, and a nanoscale three-dimensional interconnected sponge pore structure diaphragm is prepared without any additives, and the diaphragm surface is lace-like nanopores.

[0025] Specifically, during the ultrasonic atomization treatment, ultrasonic technology is used to disperse liquid water into tiny droplets, i.e., atomized water droplets. The present invention strictly controls the production rate of the atomized water droplets in this process to 0.5L / h to 20L / h, so that the atomized water droplets can contact the casting liquid wet film at this production rate and enter the first film body. Since the first membrane body is essentially a liquid membrane, that is, a cast liquid wet membrane, which contains an organic solvent phase formed by a film-forming polymer and an organic solvent, and since the organic solvent is miscible with water, and water is a non-solvent for the film-forming polymer (it cannot dissolve the film-forming polymer), the atomized water droplets can diffuse with the organic solvent in the organic solvent phase. Therefore, under the atmosphere of the atomized water droplets, the organic solvent phase system is no longer stable and gradually begins to separate into polymer-rich organic solvent phases and polymer-poor organic solvent phases, thereby achieving partial phase transformation in the liquid membrane. On this basis, when the first membrane body containing the polymer-rich organic solvent phase and the polymer-poor organic solvent phase is subsequently treated in a water bath, the organic solvent therein rapidly diffuses with water. During the phase transformation process, the polymer-rich organic solvent phase and the polymer-poor organic solvent phase are finally solidified to form an internal skeleton of the membrane and internal pores of the membrane, respectively. After the membrane is washed with water for many times, the organic solvent in the pores is fully cleaned, and finally a solid membrane including only a polymer skeleton and inorganic particles, with a high porosity and uniform pore structure is obtained, that is, an inorganic particle composite polymer membrane.

[0026] It needs additional explanation that the production rate refers to the volume of droplets produced per unit time during the ultrasonic atomization process.

[0027] The surfaces of both sides of the obtained composite membrane have a lace-like nanopore structure without a dense cortex, while the interior has a three-dimensional interconnected sponge pore structure without micropore structures such as finger-shaped pores and water droplet pores. It also has the characteristics of strong pore connectivity, small overall pore size and narrow pore size distribution.

[0028] In several typical embodiments, in order to introduce a more suitable number of atomized water droplets and a more uniform dispersion into the first film body, so that the diffusion rate between the atomized water droplets and the organic solvent is more suitable, thereby inhibiting the generation of micron-sized macropores, obtaining an inorganic particle composite polymer membrane with a better nanopore structure, and more effectively improving its electrolyte conduction and gas barrier capabilities, the production rate of the atomized water droplets in step S3 is further preferably 5L / h to 15L / h. In several more typical embodiments, since the environmental humidity can be regulated by adjusting the production rate of the atomized water droplets, and when the environmental humidity is more suitable, the pore structure of the inorganic particle composite polymer membrane finally prepared is more uniform and the pore size is suitable, and the pore connectivity is strong, so the inventors have preferably selected the environmental humidity of ultrasonic atomization treatment to be 30% to 98%, more preferably 50% to 90%, after a large number of experiments, and under this condition, an inorganic particle composite polymer membrane with a better pore structure, a more suitable porosity, higher structural stability and longer service life is obtained.

[0029] Furthermore, in order to more significantly optimize the pore structure type of the obtained composite membrane, obtain a pore structure with a more suitable pore size, and ultimately obtain a composite membrane with higher comprehensive performance, the ultrasonic atomization treatment time is preferably 0.1 min to 10 min, the temperature is preferably 25°C to 90°C, and more preferably 25°C to 35°C. Within this temperature range, a composite membrane with a more suitable porosity, higher mechanical properties and structural stability is obtained.

[0030] In the above-mentioned preparation method provided by the present invention, the immersion precipitation phase transformation process is realized by water bath treatment, the organic solvent phase in the membrane body is removed and a solid membrane is finally formed. In order to obtain a more stable membrane structure, the inventor has preferably selected the water bath treatment temperature of 15°C to 60°C, more preferably 20°C to 30°C after a large number of experiments. And, in several typical embodiments, it also includes cleaning and drying the second membrane body after the water bath treatment, and finally obtaining an inorganic particle composite polymer membrane, and the obtained composite exhibits higher comprehensive performance. And, it is preferred that the cleaning treatment is carried out by water, and the number of times is at least 3 times, so as to more effectively remove the residual organic solvent and obtain an inorganic particle composite polymer membrane with more uniform composition, internal pore size and distribution.

[0031] In several typical embodiments, the inventors have preferred the film-forming polymer to be a polysulfone polymer, more preferably one or more of polysulfone, polyethersulfone and polyphenylsulfone, through a large number of experiments, so as to more effectively optimize the pore structure and improve the various properties of the resulting composite membrane; corresponding to the type of film-forming polymer, the organic solvent is preferably a good solvent for polysulfone polymers, so as to achieve complete dissolution of the film-forming polymer and improve the structural integrity and continuity of the resulting composite membrane. In several more typical embodiments, the film-forming polymer is preferably polysulfone, and the organic solvent is preferably one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and N,N-dimethylformamide. After a large number of experiments, the inventors screened the types of film-forming polymers and corresponding organic solvents for compatibility, so that the organic solvent phase in which the film-forming polymer is dissolved can form a more obvious phase interface with the atomized water droplets, obtain pores with better surface properties, and ultimately make the resulting composite membrane have a better pore structure.

[0032] Furthermore, in order to improve the hydrophilicity of the obtained composite film, the inorganic particles are selected from one or more of zirconium dioxide, cerium dioxide, titanium dioxide and barium sulfate. In order to improve the hydrophilicity, the inventors preferred the inorganic particles to be zirconium dioxide after a large number of experiments, and thus obtained an inorganic particle composite polymer film with higher structural stability. In order to improve the physical compatibility with the film-forming polymer and obtain higher dispersibility of the inorganic particles, the particle size of the inorganic particles is preferably 20nm to 200nm, and more preferably 50nm to 100nm. The weight ratio of the inorganic particles to the film-forming polymer is preferably (5.0 to 6.0): 1, and the weight ratio of the film-forming polymer to the organic solvent is 1: (5.5 to 6.0) to further improve the mechanical properties of the obtained composite film. And, the support layer used is a porous support layer. In order to improve the mechanical properties and structural stability of the obtained composite membrane, while also taking into account its porosity and ability to transmit liquid, the thickness of the support layer is preferably 50 μm to 300 μm, and the support layer is a wire mesh structure and / or a non-woven fabric structure, more preferably a wire mesh structure, so as to minimize the impact on other properties of the diaphragm and improve the mechanical stability of the final composite membrane. In several typical embodiments, the support layer material is selected from one or more of polyphenylene sulfide, polypropylene and polytetrafluoroethylene.

[0033] In several typical embodiments, step S1 also includes: step S1-1, dissolving the film-forming polymer in an organic solvent to form a polymer solution; step S1-2, adding inorganic particles to the polymer solution, and obtaining a casting solution after mixing; preferably, the mixing is achieved by stirring and / or ball milling. In the process of preparing the casting solution, a uniform organic solution of the film-forming polymer is formed in advance, and then the inorganic particles are added thereto and mixed to obtain a uniform dispersion, i.e., the casting solution. Compared with the method of adding the film-forming mixture and the inorganic particles to the organic solvent at the same time and mixing them, this preparation method can obtain a mixed slurry system with more uniform composition and more uniform dispersion. In the process of coating to obtain the first film body, a more uniform film body can also be formed, which is more conducive to improving the effects of subsequent ultrasonic atomization treatment and water bath treatment, and obtaining a composite film with fewer defects and better performance. On this basis, in order to further improve the dispersion uniformity of the casting liquid so that the final composite membrane exhibits better comprehensive performance, especially hydrophilicity and gas barrier properties, the inventors have preferably adopted stirring as the mixing method after a large number of experiments, and the stirring rate is 100r / min~1000r / min, and the time is 24h~72h.

[0034] In the process of coating and film formation, since the bubbles in the casting liquid may affect the appearance uniformity and density of the final film body, before coating, step S2 preferably also includes degassing the casting liquid to weaken the adverse effects of bubbles on the various properties of the obtained composite film. Preferably, the degassing treatment is stirring degassing and / or vacuum degassing. And in a typical embodiment, the degassing treatment is preferably vacuum degassing, and the degassing time is 2h to 24h. At this time, the obtained composite film has fewer appearance defects, a more uniformly distributed pore structure, and also exhibits higher mechanical properties.

[0035] The second aspect of the present invention provides an inorganic particle composite polymer membrane, which is prepared by the above-mentioned method for preparing the inorganic particle composite polymer membrane. The inorganic particle composite polymer membrane is a porous structure, and the pore size is 20nm to 500nm, and the porosity is 60% to 90%; preferably, the pore size of the inorganic particle composite polymer membrane is 50nm to 220nm, and the porosity is 70% to 85%. The obtained inorganic particle composite polymer membrane has strong pore connectivity, small overall pore size and narrow pore size distribution, has a more suitable porosity, and has an excellent structure. At the same time, the inorganic particle composite polymer membrane obtained by the present invention also exhibits a higher bubble point pressure, better electrical conductivity, higher mechanical strength, and higher hydrophilicity.

[0036] The third aspect of the present invention provides an application of the above-mentioned inorganic particle composite polymer membrane as an alkaline electrolyzer diaphragm material in the field of water electrolysis hydrogen production. Because the inorganic particle composite polymer membrane prepared by the above method has excellent pore structure, superior electrolyte transmission performance and gas barrier performance, high comprehensive performance, and a wide range of applications, it is especially suitable for various different water electrolysis hydrogen production scenarios such as renewable energy water electrolysis hydrogen production or high-pressure water electrolysis hydrogen production with volatility characteristics. As a diaphragm material, it is used to block the anode and cathode gases and conduct the alkaline electrolyte, realizing efficient replacement of the traditional PPS diaphragm.

[0037] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0038] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0039] Example 1

[0040] Preparation of an inorganic particle composite polymer film:

[0041] Step S1: 204 g of N,N-dimethylacetamide is heated to 50° C. in a reaction kettle, and 36 g of polysulfone (wherein the weight ratio of the film-forming polymer polysulfone to the organic solvent N,N-dimethylacetamide is 1:5.7) is added thereto under high-speed stirring, and stirred for 48 hours to fully dissolve the polysulfone in N,N-dimethylacetamide to form a polymer solution; then 204 g of zirconium dioxide inorganic particles with a particle size of 50 nm are added to the above polymer solution (wherein the weight ratio of the zirconium dioxide inorganic particles to the film-forming polymer polysulfone is 5.7:1), and physically mixed at 50° C. and a stirring rate of 500 r / min for 48 hours to fully disperse the zirconium dioxide in the slurry to obtain a casting liquid with a uniform texture.

[0042] Step S2: The casting liquid is subjected to a vacuum degassing treatment for 6 hours, and then the casting liquid is coated on the surface of a polypropylene porous support layer having a wire mesh structure and a thickness of 150 μm to obtain a liquid membrane, namely, a first membrane body.

[0043] Step S3: Control the temperature to 30°C, and allow the first film to undergo steam-induced phase transformation under the atomization of the ultrasonic atomizing humidifier. The atomized water droplets generated by the ultrasonic atomization treatment contact the first film at a production rate of 10L / h, so that the atomized water droplets enter the internal structure of the first film, and the organic solvent in the first film is pre-evaporated. At this time, the environmental humidity provided by the ultrasonic atomization treatment is 70%; after 1 minute of ultrasonic atomization treatment (i.e., after the organic solvent is pre-evaporated for 1 minute), the second film is obtained.

[0044] Step S4: immerse the second membrane body in a water bath at 25° C. and solidify it after 8 minutes to form a diaphragm with a thickness of 450 μm. Then, wash it with deionized water for 3 times and obtain the final diaphragm product after drying.

[0045] The cross-sectional microscopic morphology of the obtained inorganic particle composite polymer film is shown in Figure 1 , surface microstructure diagram see Figure 2 , Figures 1a, 1b, 2a and 2b represent morphology images at different magnifications, where the scale bars in Figures 1a and 2a are 200 μm, and the scale bars in Figures 1b and 2b are 1 μm.

[0046] Example 2

[0047] Preparation of an inorganic particle composite polymer film:

[0048] The only difference between this embodiment and embodiment 1 is the ultrasonic atomization treatment in step S3. Specifically, the atomized water droplets produced by the ultrasonic atomization treatment contact the first film body at a production rate of 5 L / h so that the atomized water droplets enter the internal structure of the first film body, and at the same time, the organic solvent in the first film body is pre-evaporated. At this time, the environmental humidity provided by the ultrasonic atomization treatment is 50%.

[0049] Example 3

[0050] Preparation of an inorganic particle composite polymer film:

[0051] The only difference between this embodiment and embodiment 1 is the ultrasonic atomization treatment in step S3. Specifically, the atomized water droplets produced by the ultrasonic atomization treatment contact the first film body at a production rate of 15L / h so that the atomized water droplets enter the internal structure of the first film body, and at the same time, the organic solvent in the first film body is pre-evaporated. At this time, the environmental humidity provided by the ultrasonic atomization treatment is 90%.

[0052] Example 4

[0053] Preparation of an inorganic particle composite polymer film:

[0054] The only difference between this embodiment and embodiment 1 is the ultrasonic atomization treatment in step S3. Specifically, the atomized water droplets produced by the ultrasonic atomization treatment contact the first film body at a production rate of 0.5 L / h, so that the atomized water droplets enter the internal structure of the first film body, and at the same time, the organic solvent in the first film body is pre-evaporated. At this time, the environmental humidity provided by the ultrasonic atomization treatment is 30%.

[0055] Example 5

[0056] Preparation of an inorganic particle composite polymer film:

[0057] The only difference between this embodiment and embodiment 1 is the ultrasonic atomization treatment in step S3. Specifically, the atomized water droplets produced by the ultrasonic atomization treatment contact the first film body at a production rate of 20L / h, so that the atomized water droplets enter the internal structure of the first film body, and at the same time, the organic solvent in the first film body is pre-evaporated. At this time, the environmental humidity provided by the ultrasonic atomization treatment is 98%.

[0058] Example 6

[0059] Preparation of an inorganic particle composite polymer film:

[0060] The difference between this embodiment and embodiment 1 is only the ultrasonic atomization treatment in step S3. Specifically, the temperature is controlled to 90°C, and the first membrane body undergoes steam-induced phase conversion under the atomization action of the ultrasonic atomization humidifier, and the time is changed from 1 min to 0.1 min.

[0061] Example 7

[0062] Preparation of an inorganic particle composite polymer film:

[0063] The difference between this embodiment and embodiment 1 is only the ultrasonic atomization treatment in step S3. Specifically, the temperature is controlled to 25°C, and the first membrane body undergoes steam-induced phase conversion under the atomization action of the ultrasonic atomization humidifier, and the time is changed from 1 min to 10 min.

[0064] Example 8

[0065] Preparation of an inorganic particle composite polymer film:

[0066] The difference between this embodiment and embodiment 1 is only the ultrasonic atomization treatment in step S3. Specifically, the temperature is controlled to 98°C, and the first membrane body undergoes steam-induced phase conversion under the atomization action of the ultrasonic atomization humidifier, and the time is changed from 1 min to 0.05 min.

[0067] Example 9

[0068] Preparation of an inorganic particle composite polymer film:

[0069] The difference between this embodiment and embodiment 1 is only the ultrasonic atomization treatment in step S3. Specifically, the temperature is controlled to 15°C, and the first membrane body undergoes steam-induced phase conversion under the atomization action of the ultrasonic atomization humidifier, and the time is changed from 1 min to 15 min.

[0070] Example 10

[0071] Preparation of an inorganic particle composite polymer film:

[0072] The only difference between this embodiment and embodiment 1 is that in step S1 , zirconium dioxide and the polymer solution are physically mixed, specifically: the physical mixing is carried out at a stirring rate of 80 r / min for 96 hours.

[0073] Embodiment 11

[0074] Preparation of an inorganic particle composite polymer film:

[0075] The only difference between this embodiment and embodiment 1 is that in step S1 , zirconium dioxide and the polymer solution are physically mixed, specifically: the physical mixing is carried out at a stirring rate of 1200 r / min for 12 hours.

[0076] Example 12

[0077] Preparation of an inorganic particle composite polymer film:

[0078] The only difference between this embodiment and embodiment 1 is that the degassing treatment in step S2 is not performed.

[0079] Example 13

[0080] Preparation of an inorganic particle composite polymer film:

[0081] The only difference between this embodiment and embodiment 1 is that polyimide is selected as the film-forming polymer instead of polyphenylene sulfone.

[0082] Comparative Example 1

[0083] The commercial diaphragm ZIRFON PERL UTP500 was directly selected as the diaphragm sample.

[0084] Comparative Example 2

[0085] Zirmbrane produced by Carbon Energy Technology Company was directly selected as the diaphragm sample.

[0086] Comparative Example 3

[0087] Preparation of an inorganic particle composite polymer film:

[0088] The only difference between this comparative example and Example 1 is that the ultrasonic atomization treatment in step S3 is not performed, but the first membrane body is directly subjected to water bath, cleaning and drying treatment to obtain the final diaphragm product.

[0089] The cross-sectional microscopic morphology of the obtained diaphragm is shown in Figure 3 , surface microstructure diagram see Figure 4 .

[0090] Comparative Example 4

[0091] Preparation of an inorganic particle composite polymer film:

[0092] The difference between this comparative example and Example 1 is only the ultrasonic atomization treatment in step S3. Specifically, the atomized water droplets produced by the ultrasonic atomization treatment contact the first film body at a production rate of 0.2 L / h, so that the atomized water droplets enter the internal structure of the first film body, and at the same time, the organic solvent in the first film body is pre-evaporated. At this time, the environmental humidity provided by the ultrasonic atomization treatment is 12%.

[0093] Comparative Example 5

[0094] Preparation of an inorganic particle composite polymer film:

[0095] The difference between this comparative example and Example 1 is only the ultrasonic atomization treatment in step S3. Specifically, the atomized water droplets produced by the ultrasonic atomization treatment contact the first film body at a production rate of 25 L / h, so that the atomized water droplets enter the internal structure of the first film body, and at the same time, the organic solvent in the first film body is pre-evaporated. At this time, the environmental humidity provided by the ultrasonic atomization treatment is 99.99%.

[0096] Test Method

[0097] Bubble point pressure: Indicates the minimum gas pressure at which gas penetrates the diaphragm material and produces the first string of bubbles, measured according to GB / T32361-2015.

[0098] Surface resistance: It refers to the resistance of the diaphragm material to the transfer of electrolyte per unit area.

[0099] Mechanical strength: measured according to GB1040.3-2006.

[0100] Average pore size: measured together with bubble point pressure according to GB1040.3-2006.

[0101] Alkali loss: The mass ratio of diaphragm material lost due to chemical reaction between diaphragm material and alkali solution in hot alkaline environment. Measured according to SJ / T 10171.6-91, the smaller the value, the better the chemical stability of the diaphragm sample.

[0102] Table 1

[0103]

[0104]

[0105] From the above description, it can be seen that the above-mentioned embodiments of the present invention have more outstanding comprehensive performance, with high gas barrier properties, high porosity, strong hydrophilicity and low surface resistance, as well as excellent mechanical stability and chemical stability, and have important industrial application potential.

[0106] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an inorganic particle composite polymer film, characterized in that: The method for preparing the inorganic particle composite polymer film comprises: Step S1, adding a film-forming polymer and inorganic particles into an organic solvent to form a film casting solution; Step S2, coating the casting liquid on at least one side surface of the support layer to form a first film body carrying a wet film of the casting liquid; Step S3, performing ultrasonic atomization treatment on the first film body so that the atomized water droplets are in wet contact with the casting liquid at a production rate of 0.5L / h to 20L / h to obtain a second film body; Step S4, performing water bath treatment on the second film body to obtain the inorganic particle composite polymer film.

2. The method for preparing an inorganic particle composite polymer film according to claim 1, characterized in that: In step S3, the production rate of the atomized water droplets is 5L / h to 15L / h; Preferably, the humidity of the environment for ultrasonic atomization treatment is 30% to 98%, more preferably 50% to 90%.

3. The method for preparing an inorganic particle composite polymer film according to claim 1 or 2, characterized in that: The ultrasonic atomization treatment is performed for a time of 0.1 min to 10 min at a temperature of 25° C. to 90° C., preferably 25° C. to 35° C.

4. The method for preparing an inorganic particle composite polymer film according to any one of claims 1 to 3, characterized in that: The temperature of the water bath treatment is 15°C to 60°C, preferably 20°C to 30°C.

5. The method for preparing an inorganic particle composite polymer film according to any one of claims 1 to 4, characterized in that: The film-forming polymer is a polysulfone polymer, preferably one or more of polysulfone, polyethersulfone and polyphenylsulfone, more preferably polysulfone; The organic solvent is a good solvent for the polysulfone polymer, and is preferably one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and N,N-dimethylformamide.

6. The method for preparing an inorganic particle composite polymer film according to any one of claims 1 to 5, characterized in that: The inorganic particles are selected from one or more of zirconium dioxide, cerium dioxide, titanium dioxide and barium sulfate, preferably zirconium dioxide; and / or, The particle size of the inorganic particles is 20 nm to 200 nm, preferably 50 nm to 100 nm; and / or, The weight ratio of the inorganic particles to the film-forming polymer is (5.0-6.0):1, and the weight ratio of the film-forming polymer to the organic solvent is 1:(5.5-6.0); The thickness of the support layer is 50 μm to 300 μm, and the support layer is a wire mesh structure and / or a non-woven fabric structure, preferably a wire mesh structure; More preferably, the support layer material is selected from one or more of polyphenylene sulfide, polypropylene and polytetrafluoroethylene.

7. The method for preparing an inorganic particle composite polymer film according to any one of claims 1 to 6, characterized in that: Step S1 also includes: Step S1-1, dissolving the film-forming polymer in the organic solvent to form a polymer solution; Step S1-2, adding the inorganic particles into the polymer solution, and obtaining the casting solution after mixing; Preferably, the mixing is achieved by stirring and / or ball milling; Preferably, the mixing is achieved by stirring, and the stirring rate is 100 r / min to 1000 r / min, and the time is 24 h to 72 h.

8. The method for preparing an inorganic particle composite polymer film according to any one of claims 1 to 7, characterized in that: Before the coating is performed, step S2 further includes degassing the casting solution; Preferably, the degassing treatment is stirring degassing and / or vacuum degassing; More preferably, the degassing treatment is vacuum degassing, and the degassing time is 2h to 24h.

9. An inorganic particle composite polymer film, characterized in that: The inorganic particle composite polymer membrane is prepared by the method for preparing an inorganic particle composite polymer membrane according to any one of claims 1 to 8. The inorganic particle composite polymer membrane has a porous structure with a pore size of 20nm to 500nm and a porosity of 60% to 90%.

10. Use of the inorganic particle composite polymer membrane according to claim 9 as a diaphragm material for an alkaline electrolytic cell in the field of hydrogen production by water electrolysis.